2004
DOI: 10.1007/s10499-004-1024-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth and survival of white shrimp postlarvae (Litopenaeus vannamei) fed dried Artemia biomass versus four commercial feeds and three crustacean meals

Abstract: The use of dried Artemia biomass meal as an exclusive feed for postlarval white shrimp (Litopenaeus vannamei) was compared with four commercial feeds and three crustacean meals in a series of trials. Postlarvae (PL1-PL6) were stocked at a density of 1.5-2.5/litres in 16 tanks (100 litres volume) and fed, ad libidum, five times a day, over 23-29 days. Feeding postlarval shrimp with dried Artemia biomass resulted in a significantly larger size than feeding with three of the commercial feeds, and the crustacean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…The results of this study are in agreement with those of Abelin, Tackaert and Sorgeloos (1989), who reported that PL30‐45 of P. monodon and PL15 of P. vannamei fed a diet containing a freeze‐dried Artemia meal had a significantly better growth as compared with the FM‐based diet. Naegel and Rodriguez‐Astudillo (2004) demonstrated that feeding L. vannamei shrimp PL with dried Artemia biomass resulted in a significantly higher survival and larger size compared with four commercial feeds and three crustacean meals. Moreover, juvenile American lobsters ( Homarus americanus ) fed enriched frozen adult Artemia showed the greatest weight gain (>6% day −1 ) compared with formulated diets (Tlusty et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in agreement with those of Abelin, Tackaert and Sorgeloos (1989), who reported that PL30‐45 of P. monodon and PL15 of P. vannamei fed a diet containing a freeze‐dried Artemia meal had a significantly better growth as compared with the FM‐based diet. Naegel and Rodriguez‐Astudillo (2004) demonstrated that feeding L. vannamei shrimp PL with dried Artemia biomass resulted in a significantly higher survival and larger size compared with four commercial feeds and three crustacean meals. Moreover, juvenile American lobsters ( Homarus americanus ) fed enriched frozen adult Artemia showed the greatest weight gain (>6% day −1 ) compared with formulated diets (Tlusty et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Live adult Artemia is also an ideal food for ornamental fish (Lim et al 2001). According to Naegel and Rodriguez‐Astudillo (2004), dried Artemia is a well‐suited feed for postlarval Litopenaeus vannamei .…”
Section: Introductionmentioning
confidence: 99%
“…2002). Furthermore, dried Artemia is a well‐suited feed for postlarval Litopenaeus vannamei shrimp (Naegel & Rodriguez‐Astudillo 2004) and for postlarval prawn, Macrobrachium rosenbergii (Anh et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(1989) who reported that PL 30–45 Penaeus monodon and PL15 P. vannamei receiving a diet containing freeze‐dried Artemia meal had a significantly better growth when compared to the FM‐based control diet. Naegel & Rodriguez‐Astudillo (2004) illustrated that feeding Litopenaeus vannamei shrimp PL with dried Artemia biomass resulted in a significant higher survival and larger size compared to four commercial feeds and three crustacean meals.…”
Section: Discussionmentioning
confidence: 99%
“…2001; Le et al. 2008), shrimp (Naegel & Rodriguez‐Astudillo 2004; Van et al. 2008), prawn (New 2002) and crab (Ut et al.…”
Section: Introductionmentioning
confidence: 99%